Corneal Endothelial Cell Loss after Cataract Extraction by Phaecoemulsification versus Conventional Extra Capsular Cataract Extraction Technique: Phaecoemulsification Versus Conventional Cataract Extraction Technique - Khoso, Ayaz Ali; Pirzado, Imran Ali; Bhutto, Shabeer Ahmed; Gopang, Zakaullah; Kandhro, Prince Aakash Gul; Azam, Muhammad (Pakistan Journal of Health Sciences, 2025)
A cataract is a condition affecting the eye in which the lens, previously clear, has developed cloudiness and flexibility, obstructing the passage of light. This condition progressively deteriorates and is a significant contributor to global blindness. A cataract is identified through a thorough examination of the pupil using a torch light and a slit lamp, both in dilated and non-dilated states. In 1967, Charles Kelman introduced phacoemulsification, an innovative surgical technique for the treatment of cataracts. Objective: To compare the corneal endothelial cell loss after cataract extraction performed with conventional extra capsular cataract extraction versus standardized Phacoemulsification. Methods: Non-randomized clinical trial study was conducted at Department of Ophthalmology, Chandka Medical Hospital Shaheed Mohtrama Benazir Bhutto Medical University Larkana in time frame of six months by using probability consecutive sampling technique. Data analysis was performed by using SPSS version 24.0. The Chi-square test was utilized for cross-tabulation. Results: In comparison to individuals receiving ECCE, those undergoing PHACO tended to be younger and exhibited a greater proportion of females. While the PHACO group consistently exhibited a higher endothelial cell count during all post-operative intervals, both techniques led to a significant decrease in the number of endothelial cells observed post-operation. Conclusion: The present study supported the common understanding that phacoemulsification is linked to a significantly reduced incidence of endothelial cell loss.